Lactobacillus paracasei N1115 alleviates hyperuricemia in mice: regulation of uric acid metabolism as well as its impact on gut microbiota and short-chain fatty acids - Zhang, Hongyu; Wang, Da; Li, Dongning; Bao, Bingkun; Chen, Qian; Wang, Sunhaoran; Han, Shichao; Zhao, Mengge (Frontiers in Nutrition, 2025)
Hyperuricemia (HUA) is a worldwide metabolic disorder characterized by abnormally elevated serum uric acid (SUA) levels, and recent studies suggest that probiotics have potential in mitigating HUA. This study aimed to evaluate the efficacy of Lactobacillus paracasei N1115 in alleviating HUA in mice and explore its underlying mechanisms. The results demonstrated that both high and low-dose L. paracasei N1115 reduced SUA levels in vivo by 29.18 and 27.29%, respectively (p < 0.05), effectively mitigating HUA. Additionally, the probiotic protected renal function, mitigated tissue damages and inflammation. Mechanically, it effected uric acid (UA) metabolism by regulating the UA-production related enzymes xanthine oxidase (XOD), adenosine deaminase (ADA), and 5′-nucleotidase (5′-NT), as well as the urate transpoters urate transporter 1 (URAT1) and glucose transporter 9 (GLUT9), and organic anion transporter 3 (OAT3). Moreover, L. paracasei N1115 reshaped the gut microbiota and significantly increased the abundance of Bifidobacterium, while modulating renal metabolism and elevating butyric acid levels in gut. These findings suggest that L. paracasei may alleviate HUA by enhancing butyrate levels through a cross-feeding interaction with Bifidobacterium. Although further experiments are required to substantiate underlying mechanisms, this study provides a basis for HUA-targeting functional foods research.